Antitumor effect of YM155, a novel small-molecule survivin suppressant, via mitochondrial apoptosis in human MFH/UPS - MINODA, MASAYA (Int J Oncol, 2015)
Survivin is a member of the inhibitor of apoptosis family, which is known to inhibit mitochondrial apoptosis. Survivin is highly expressed in cancers and plays an important role in cancer cell survival, and increased survivin expression is an unfavorable prognostic marker in cancer patients. YM155, a novel small-molecule survivin suppressant, selectively suppresses survivin expression, resulting in the induction of apoptosis in various malignancies. However, the roles of survivin in human malignant fibrous histiocytoma/undifferentiated pleomorphic sarcoma (MFH/UPS) have not been studied. In the present study, we examined survivin expression in human musculoskeletal tumor tissues, and the effect of survivin inhibition by siRNA or YM155 on apoptotic activity in human MFH/UPS cell lines. In tumor tissues, mRNA expression of survivin was significantly higher in MFH/UPS samples than in benign schwannomas. Moreover, in vitro studies revealed that both survivin siRNA and YM155 suppressed survivin expression and inhibited MFH/UPS cell proliferation in a dose- and a time-dependent manner. Further, the numbers of apoptotic cells significantly increased with YM155 treatment. In vivo, tumor volume in YM155-treated groups was significantly reduced without significant bodyweight loss. Increased apoptotic activity along with decreased survivin expression was also observed in YM155-treated tumors. The findings in this study strongly suggest that survivin suppressants, including YM155, contribute to the suppression of human MFH/UPS cell growth via promoting mitochondrial apoptosis, and that survivin may be a potent therapeutic target for the novel treatment of human MFH/UPS.